ПИРОЛИЗ ҚУРИЛМАЛАРИНИНГ ЗАМОНАВИЙ ҲОЛАТИ ТАҲЛИЛИ - Хатамов, Иномжон; Ибрагимов, Умиджон (Innovatsion texnologiyalar, 2022)
This article presents the relevance of the use of pyrolysis plants designed for processing biomass and obtaining liquid, solid and gaseous fuels from it, characteristics, types, elemental composition and physical properties of biomass, types of reactors for pyrolysis plants, technological schemes for organizing the process.